2016
DOI: 10.18559/ebr.2016.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the portrayal of 50+ consumers in Polish print advertising

Abstract: BOOK REVIEWSMariusz E. Sokołowicz, Rozwój terytorialny w świetle dorobku ekonomii instytucjonalnej. Przestrzeń -bliskość - Abstract : This article raises an issue of consumers at the age of 50+. The role of this market segment is constantly growing in Poland, but despite of this, it is still hard to identify this wide consumer group. Therefore, the aim of the paper is to identify the portrayal of older people (50+) in Polish print advertising. Amongst over-fifty consumers, the press media are still the key co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Older Polish consumers might enjoy new and exciting experiences but of a different nature than younger generations. While young Poles usually associate experiences with physicality, older consumers prefer spiritual or mental aspects of experiences (Badowska and Rogala, 2016). In Poland, cultural patterns limiting the activity of older people are visible.…”
Section: Retail Customer Experiencementioning
confidence: 99%
“…Older Polish consumers might enjoy new and exciting experiences but of a different nature than younger generations. While young Poles usually associate experiences with physicality, older consumers prefer spiritual or mental aspects of experiences (Badowska and Rogala, 2016). In Poland, cultural patterns limiting the activity of older people are visible.…”
Section: Retail Customer Experiencementioning
confidence: 99%
“…The authors praise the campaign for its inclusivity and for not promoting an unrealistic image of old age. Regarding Poland, Badowska and Rogala (2016) investigated the portrayal of older adults (50+) in selected Polish print magazines with high readership (31 issues total). The results showed that the portrayal of people aged 50-59 was predominantly positive, whereas the elderly (60+) were hardly present in the research material.…”
Section: Introduction: Representation Of Older Adults In Media and Ad...mentioning
confidence: 99%